1993
DOI: 10.1055/s-2007-1010385
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Ultrasonography in the Local Staging of Primary Gastric Lymphoma

Abstract: Endoscopic ultrasonography (EUS) and endoscopy were prospectively performed and compared to the histopathologic findings of the resection specimens in 24 patients with primary gastric lymphoma (PGL). On EUS, three types of PGL could be differentiated, a superficial type (n = 10), an infiltrating type (n = 12) and a tumorous type (n = 2). In the correct assessment of surface extension of the tumors, endoscopy and EUS agreed in 37.5% of cases and EUS showed more extensive disease than endoscopy in 58% of cases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(54 citation statements)
references
References 0 publications
3
47
0
4
Order By: Relevance
“…In patients who had lymphoma restricted to the stomach, upper endoscopy and upper ultrasound endoscopy were performed. 33 Additional radiologic studies were performed according to the primary anatomic site of disease, such as magnetic resonance imaging of the salivary glands or orbit.…”
Section: Baseline and Outcome Assessmentsmentioning
confidence: 99%
“…In patients who had lymphoma restricted to the stomach, upper endoscopy and upper ultrasound endoscopy were performed. 33 Additional radiologic studies were performed according to the primary anatomic site of disease, such as magnetic resonance imaging of the salivary glands or orbit.…”
Section: Baseline and Outcome Assessmentsmentioning
confidence: 99%
“…For established gastric cancer, EUS is superior to CT in assessing locoregional stage 20 , although three dimensional multidetector row CT techniques have improved accuracy 21 . In patients with gastric lymphoma, EUS is particularly accurate in assessing T stage 22 . EUS‐FNA is valuable for lymph node sampling and biopsying the gastric wall when the EUS appearance is abnormal but mucosal biopsies are non‐diagnostic.…”
Section: Gastric Cancermentioning
confidence: 99%
“…The depth of infiltration was evaluated as previously described. 14 Lymph nodes detected around the duodenum and stomach were considered as infiltrated by lymphoma at EUS if they were spherical, hypoechogenic, and 1 cm or more in diameter. The echo endoscopists were blinded as to the detailed results of histology, and the pathologists were blinded to the results of EUS staging.…”
Section: Patients and Inclusion Criteriamentioning
confidence: 99%
“…Its value for such detection was also demonstrated in our previous study. 14 Discrepancies between diVerent response rates may be due not only to nodal involvement but also to the depth of wall invasion. Eidt et al demonstrated that the probability of lymph node infiltration increased when it was correlated with the depth of gastric wall infiltration.…”
Section: Initial Stage Of the Tumourmentioning
confidence: 99%